Neural correlates of behavioral variation in healthy adults' antisaccade performance. (19th February 2013) - Schaeffer, David J.; Amlung, Michael T.; Li, Qingyang; Krafft, Cynthia E.; Austin, Benjamin P.; Dyckman, Kara A.; McDowell, Jennifer E.
Abstract Cognitive control is required for correct antisaccade performance. High antisaccade error rates characterize certain psychiatric disorders, but can be highly variable, even among healthy groups. Antisaccade data were acquired from a large sample of healthy undergraduates, and error rate was quantified. Participants who reliably made few errors (good, n = 13) or many errors (poor, n = 13) were recruited back to perform antisaccades during fMRI acquisition. A data‐derived model was used to compare signal between good and poor performers during blocks of antisaccade trials. Behaviorally derived regressors were used to compare signal between good and poor performers during correct and error trials. Results show differential activation in middle frontal gyrus and inferior parietal lobule between good and poor performers, suggesting that failure to recruit these top‐down control regions corresponds to poor antisaccade performance in healthy young adults.